Digital marketing development trends - KALINA, I. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The trends of development of digital marketing were investigated using statistical data on Internet users in U.S., obtained from a study performed by Pew Research Center at the beginning of 2019, and in Ukraine, obtained from a study performed by the research holding Factum Group Ukraine on the initiative of International Association of Ukraine in ІІІ quarter 2018 and 2019. The data were collected by the following criteria: age, gender, education, region and finances. Data analysis for the two countries showed the same result. The technological awareness of the society increases every year, which leads to more efficient management, sales, transportation and financial services for the consumers/clients of the enterprise. Indicators also show that both children and adults, people living in the city and in the countryside, people who are financially independent and people with both middle and low income, people with higher education and professional primary education, they all use the Internet. For communication, making purchases, doing research etc. Society has gone digital and businesses need to adapt by changing their management practices. Marketers are creating ways to promote businesses by leveraging new technology. Marketing plays a key role in the digital revitalization of any enterprise. It is through digital marketing that consumers and businesses learn about certain events (legal, economic, social, religious, etc.), and not only are they being informed, they can also inform others. Mobile devices, the Internet, local area networks, digital television and other media can also be used to collect information and conduct marketing research.